Mechanism and Optimized Design of Vehicle Quiescent Current. Issue 3 (February 2020) - Li, Qing; Li, Chuang; Hu, Mingxin; Ding, Guohui
Abstract: This paper analysed the quiescent current generation mechanism of vehicles and the four stages of quiescent current presentation during the vehicle rest process. Then the quiescent current is optimized from the perspective of ECU and vehicle electrical design. Finally, standardized recommendations for test rectification were proposed.